The endogenous calpain inhibitor calpastatin attenuates axon degeneration in murine Guillain‐Barré syndrome. Issue 1 (18th November 2022) - McGonigal, Rhona; Cunningham, Madeleine E.; Smyth, Duncan; Chou, Michael; Barrie, Jennifer A.; Wilkie, Andrew; Campbell, Clare; Saatman, Kathryn E.; Lunn, Michael; Willison, Hugh J.
Abstract: Axon degeneration accounts for the poor clinical outcome in Guillain‐Barré syndrome (GBS), yet no treatments target this key pathogenic stage. Animal models demonstrate anti‐ganglioside antibodies (AGAb) induce axolemmal complement pore formation through which calcium flux activates the intra‐axonal calcium‐dependent proteases, calpains. We previously showed protection of axonal components using soluble calpain inhibitors in ex vivo GBS mouse models, and herein, we assess the potential of axonally‐restricted calpain inhibition as a neuroprotective therapy operating in vivo. Using transgenic mice that over‐express the endogenous human calpain inhibitor calpastatin ( hCAST ) neuronally, we assessed distal motor nerve integrity in our established GBS models. We induced immune‐mediated injury with monoclonal AGAb plus a source of human complement. The calpain substrates neurofilament and AnkyrinG, nerve structural proteins, were assessed by immunolabelling and in the case of neurofilament, by single‐molecule arrays (Simoa). As the distal intramuscular portion of the phrenic nerve is prominently targeted in our in vivo model, respiratory function was assessed by whole‐body plethysmography as the functional output in the acute and extended models. hCAST expression protects distal nerve structural integrity both ex and in vivo, as shown by attenuation of neurofilament breakdown by immunolabelling and Simoa. In an extended in vivo model, while mice still initially undergo respiratory distress owing to acute conduction failure, the recovery phase was accelerated by hCAST expression. Axonal calpain inhibition can protect the axonal integrity of the nerve in an in vivo GBS paradigm and hasten recovery. These studies reinforce the strong justification for developing further animal and human clinical studies using exogenous calpain inhibitors.